The effect of the BLUI blanket on the reduction of bilirubin levels in neonatal jaundice: a preliminary clinical study - Fadilah, Tubagus Ferdi; Adisasmita, Asri C.; Ascobat, Purwantyastuti; Siswanto, Johanes Edy; Koestoer, Raldi Artono; Susianti, Yanti; Irwan, Hermansyah; Gunarsih, Arum; Heryana, Ade (Indonesian Pediatric Society, 2025)
Background Neonatal jaundice is a prevalent condition in newborns, characterized by elevated bilirubin levels. Conventional phototherapy treatments for neonatal jaundice typically require hospital admission, separation from mothers, and may interfere with breastfeeding and bonding. The Blue Light Universitas Indonesia (BLUI) LED phototherapy blanket was developed to address these limitations by providing a portable, home-based alternative that maintains mother-infant contact while delivering effective therapy. Objective To evaluate the efficacy of the Blue Light Universitas Indonesia (BLUI) LED phototherapy blanket in reducing bilirubin levels in infants with physiological jaundice. Methods A preliminary study was conducted from December 2022 to February 2023, involved 14 infants with physiological jaundice at Hermina Hospital Ciputat, Sariasih Hospital Ciputat, and the General Hospital of South Tangerang. The inclusion criteria were infants with physiological jaundice, gestational age ≥35 weeks, and birth weight ≥2,000 grams. The dependent variable was the reduction in total serum bilirubin levels, assessed by spectrophotometry. Paired sample T-test was used to compare bilirubin levels before and 24 hours after intervention with the BLUI Blanket. Results The study included 14 infants, with a mean age of 6.86 days and mean gestational age of 37.71 weeks. The BLUI Blanket demonstrated a mean bilirubin reduction of 3.11 mg/dL after 24 hours of continuous treatment, with a 19.02% decrease. The intervention was well-tolerated, with minimal adverse effects, such as maculopapular skin rash occurring in only one infant. Conclusion The BLUI Blanket is an effective and safe phototherapy device for reducing bilirubin levels in infants with physiological jaundice. This preliminary study supports further research to confirm these findings in larger populations.